2001
DOI: 10.1179/016164101101198668
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patterns in cardio–embolic infarction in a population-based study

Abstract: The study demonstrates that clinical-radiological causes and outcome of cardio-embolic infarcts in a population-based study correspond to a well-identified stroke pattern. Cardio-embolic infarcts was diagnosed in 882 cases (37.9%) of 2,330 consecutive first-ever stroke patients included in a prospective population-based stroke registry over a 14-year period (1985-1997). Thirty-three criteria out of 98 were introduced into a monovariate analysis and the significant variable were introduced into a multivariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
9
1
7
Order By: Relevance
“…Another CT-based study in patients with probable cardioembolic stroke could demonstrate a high rate of lobar and subcortical territorial infarctions. 20 In contrast to these findings the number of male patients with symptomatic ICA disease was significantly higher, which is not surprising with regard to the higher prevalence of risk factors such as hyperlipidemia and history of smoking in men. Correspondingly, male patients had more often asymptomatic or symptomatic high grade or subtotal ICA stenosis or occlusion as compared to women.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Another CT-based study in patients with probable cardioembolic stroke could demonstrate a high rate of lobar and subcortical territorial infarctions. 20 In contrast to these findings the number of male patients with symptomatic ICA disease was significantly higher, which is not surprising with regard to the higher prevalence of risk factors such as hyperlipidemia and history of smoking in men. Correspondingly, male patients had more often asymptomatic or symptomatic high grade or subtotal ICA stenosis or occlusion as compared to women.…”
Section: Discussioncontrasting
confidence: 50%
“…With regard to stroke etiology, women showed a significantly higher rate of AF in accordance with earlier studies demonstrating that women have a significantly higher risk for AF related AIS. 19,20 This might explain the higher number of territorial strokes in our female study population. Another CT-based study in patients with probable cardioembolic stroke could demonstrate a high rate of lobar and subcortical territorial infarctions.…”
Section: Discussionmentioning
confidence: 83%
“…Previous use of antiplatelet drugs was reported by 642 (41%) of the 1582 patients. The antiplatelet drugs were as follows: aspirin alone (494 patients), clopidogrel alone (70), aspirin and clopidogrel (36), aspirin and dipyridamole (14), combination of aspirin, aspirin-extendedrelease dipyridamole, and clopidogrel (1), combination of aspirin and aspirin-extendedrelease dipyridamole (1), aspirin-extendedrelease dipyridamole (4), dipyridamole (9), ticlopidine alone (3), and not documented (10). Table 1 shows the baseline demographic and clinical characteristics of patients according to previous use of antiplatelet drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported similar or lower rates of previous antiplatelet treatment. [13][14][15] In the Oxford vascular study, 80 (46%) of the 174 patients with either minor stroke or transient ischemic attack were receiving antiplatelet treatment before the event. 13 In a French prospective registry of 2330 consecutive patients with new stroke, antiplatelet treatment was used in 354 (15%) of the patients before onset of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Широкое внедрение кардиологических методов диагностики в клиническую ангионеврологиче-скую практику значительно обогатило знания о состоянии сердца у больных с ишемическим инсультом и способст-вовало углублению понимания роли сердца в генезе ин-сульта [2]. Данные регистров инсульта свидетельствуют о том, что 22-39% ишемических нарушений мозгового кро-вообращения развиваются вследствие кардиогенной эм-болии [3,4]. На сегодняшний день известно более 20 кар-диальных нарушений, ассоциированных с кардиоэмболи-ческим инсультом (КЭИ) [5].…”
unclassified